Alcohol Consumption Milestones: Comparing First- Versus Last-Reported Age of Onset. Issue 4 (4th July 2017) - Rogers, Michelle L.; Jackson, Kristina M.
ABSTRACT: Multiple assessments of age of onset of alcohol use milestones may produce inconsistent reports, yielding potentially different results, depending on the report utilized. Using data from a prospective study of 1, 023 middle school students, we modeled risk of onset of four drinking milestones as a function of multiple correlates of alcohol use and compared models using first- versus last-reported age for each milestone. While forward telescoping was evident, no significant differences were obtained for any models examined. Substantive conclusions about associations of correlates of early drinking are not greatly impacted by misreporting age of first use.